Global Existence for Functional Differential Equations with State-Dependent Delay - Mouffak Benchohra; Imene Medjadj; Juan J. Nieto; P. Prakash (Journal of Function Spaces and Applications)
Our aim in this work is to study the existence of solutions of a functional differential equation with state-dependent delay. We use Schauder's fixed point theorem to show the existence of solutions.